Abalone Muscle Texture Evaluation and Prediction Based on TPA Experiment. (20th September 2017) - Dong, Jiaxu; Fang, Xiaoyan; Wang, Huihui; Zhang, Xu; Tao, Xueheng
Abstract : The effects of different heat treatments on abalones' texture properties and sensory characteristics were studied. Thermal processing of abalone muscle was analyzed to determine the optimal heat treatment condition based on fuzzy evaluation. The results showed that heat treatment at 85°C for 1 hour had certain desirable effects on the properties of the abalone meat. Specifically, a back propagation (BP) neural network was introduced to predict the equations of statistically significant sensory hardness, springiness, and smell using the texture data gained through TPA (texture profile analysis) experiments as input and sensory evaluation data as the desired output. The final outcome was that the predictability was proved to be satisfactory, with an average error of 6.93%.